Consumo de alcohol en los estudiantes del Colegio de Bachillerato “Primero de Mayo” del cantón Yantzaza y sus efectos, en la actualidad. - Pérez Anguasha, Ana Carlota (2024)
Alcohol consumption is a problem that constantly affects society, especially adolescents who are subjected to social risk factors linked to this trend. However, when young people have the habit of ingesting psychotropic beverages their intellectual, emotional and physical capacities are seriously compromised. This affects academic performance, health and the quality of the individual's social relationships, and even threatens the young person's future in terms of work, family and professional life. Based on this dilemma, the present research aims to analyze the impact of alcohol consumption and its effects on the students of the “Primero de Mayo” High School in the Yantzaza canton. To achieve this purpose, we first conducted a literature review, which shows that in Ecuador people are starting to consume alcohol at an increasingly younger age. This has a considerable impact on their physical, mental, emotional and professional lives. Therefore, through the survey technique, a structured questionnaire was applied to 265 of the selected educational unit. The results indicate that 15% of the adolescents who participated in the study have high levels of alcohol consumption and are not fully aware of the long-term effects of this practice. Hence, in order to contribute to the resolution of this problem, some educational tools are left in the institution to provide more guidance on the subject to young people and other parties related to the institution.